2019
DOI: 10.1080/10409238.2019.1687420
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal regulation of PCNA ubiquitination in damage tolerance pathways

Abstract: DNA is constantly exposed to a wide variety of exogenous and endogenous agents, and most DNA lesions inhibit DNA synthesis. To cope with such problems during replication, cells have molecular mechanisms to resume DNA synthesis in the presence of DNA lesions, which are known as DNA damage tolerance (DDT) pathways. The concept of ubiquitination-mediated regulation of DDT pathways in eukaryotes was established via genetic studies in the yeast Saccharomyces cerevisiae, in which two branches of the DDT pathway are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 230 publications
(436 reference statements)
1
19
0
Order By: Relevance
“…In S phase, ssDNA gaps are preferentially repaired by a recombination-like mechanism called template switch (TS) that depends on the Rad18 and Rad5 E3 ubiquitin ligases, recombination proteins, including Rad51 and Rad52, and nucleases such as the Sgs1-Top3-Rmi1 (STR) complex [ 54 ]. In G2 phase, ssDNA gaps can be also filled by one of translesion synthesis (TLS) low-fidelity polymerases in a Rad18-depedendent manner [ 55 ]. In budding yeast, DSBs are predominantly repaired by homologous recombination (HR) with only a minor role of non-homologous end joining (NHEJ) that depends on the yKU (Yku70-Yku80) complex and the DNA ligase IV Dnl4 [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In S phase, ssDNA gaps are preferentially repaired by a recombination-like mechanism called template switch (TS) that depends on the Rad18 and Rad5 E3 ubiquitin ligases, recombination proteins, including Rad51 and Rad52, and nucleases such as the Sgs1-Top3-Rmi1 (STR) complex [ 54 ]. In G2 phase, ssDNA gaps can be also filled by one of translesion synthesis (TLS) low-fidelity polymerases in a Rad18-depedendent manner [ 55 ]. In budding yeast, DSBs are predominantly repaired by homologous recombination (HR) with only a minor role of non-homologous end joining (NHEJ) that depends on the yKU (Yku70-Yku80) complex and the DNA ligase IV Dnl4 [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also showed that Sb(III) causes perturbation of DNA synthesis leading to formation of ssDNA regions, which may correspond to stalled replication forks and/or ssDNA gaps formed behind the fork as a result of damage bypass ( Figure 3 E or Figure 5 B). Post-replication repair of ssDNA gaps requires two ubiquitin ligases Rad18 and Rad5 as well as HR proteins [ 54 , 55 ]. Consistently, rad18 Δ and rad5 Δ mutants were more sensitive to Sb(III) compared to wild-type ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCNA surrounds and slides along the DNA in the nucleus. DNA polymerase, helicase, exonuclease, ligase, cell cycle regulator, acetyltransferase, chromatin reconstitution and histone chaperone interact with DNA by binding with PCNA [22] PCNA was expressed in all cell cycles of normal tissues, and its expression level was relatively stable [23]. Some rabbit experiments [24] showed that the level of PCNA expression was signi cantly reduced by the stimulation of traumatic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, this modification is carried out by the E2-E3 complex Rad6-Rad18. In humans, however, several proteins seem to be implicated and their dynamics is not fully understood yet (186). Preferentially, the mono-ubiquitin mark would be extended to a poly-ubiquitin chain in a UBC13-dependent manner to stimulate ZRANB3-driven RF reversal and the error-free TS pathway in early S-phase (100,103,187,188).…”
Section: Dna Damage Tolerance Pathwaysmentioning
confidence: 99%